BIBLIOTHERAPY AND THE ROLE OF LIBRARIANS AS MENTAL HEALTH FACILITATORS - Arianti Elsa Candra; Ursa Agniya; Verry Mardiyanto (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
The increase in mental health problems, especially among students, requires actions that do not solely rely on formal clinical services. One non-clinical method that is considered relevant, affordable, and easily accessible is bibliotherapy, especially in the context of libraries as community-based places. The purpose of this article is to explore the role of librarians as non-clinical mental health supporters through the implementation of developmental bibliotherapy in libraries. The methodology used in this study was a qualitative approach with a Systematic Literature Review (SLR) of nineteen relevant scientific articles published between 2015 and 2025. The research findings indicate that developmental bibliotherapy has the potential to provide initial psychosocial support, such as the development of emotional literacy, coping skills, and reduction of stress and anxiety levels among users, especially students. In practice, librarians play a key role in curating reading materials, facilitating access to reflective information, and creating a safe environment that supports mental well-being without violating non-clinical role boundaries. Thus, the implementation of bibliotherapy also faces various ethical and professional challenges, especially those related to the boundaries of the librarian's role, user privacy protection, and the need for training and interprofessional collaboration. This article emphasizes the role of librarians as facilitators of mental health based on bibliotherapy in university libraries in Indonesia, and also provides practical suggestions for service development and improving librarians' skills in mental health literacy.